2021
DOI: 10.1002/mabi.202100042
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine‐Engineered Exosomes for Enhanced Tumor Cell Uptake and Intracellular Antitumor Drug Delivery

Abstract: Exosomes derived from non‐tumor cells hold great potential as drug delivery vehicles because of their good biosafety and natural transference of bioactive cargo between cells. However, compared to tumor‐derived exosomes, efficient delivery is limited by their weak interactions with tumor cells. It is essential to engineer exosomes that improve tumor cellular internalization efficiency. A simple and effective strategy to enhance tumor cell uptake by engineering the exosome membrane lipids can be established by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…SHEDs at passage 3 were utilized for exosome production. Exosomes were purified by several ultracentrifugation and filtration steps according to previous work [ 57 ], and the detailed procedures are shown in Supplementary Information. Two kinds of exosomes were gained from different culture conditions, named as Exo and H-Exo.…”
Section: Methodsmentioning
confidence: 99%
“…SHEDs at passage 3 were utilized for exosome production. Exosomes were purified by several ultracentrifugation and filtration steps according to previous work [ 57 ], and the detailed procedures are shown in Supplementary Information. Two kinds of exosomes were gained from different culture conditions, named as Exo and H-Exo.…”
Section: Methodsmentioning
confidence: 99%
“…Based on this, Waqas et al demonstrated that erythrocytes-derived exosomes loaded with ASOs and Cas9mRNA could inhibit the proliferation of acute myeloid leukemia and breast cancer cells in vitro and in vivo ( Usman et al, 2018 ). Recently, Zhan et al demonstrated that erythrocytes-derived exosomes modified with phosphatidylcholine and then loaded with DOX could decrease the proliferation of glioma cells via enhanced cancer cell uptake and improve intracellular DOX delivery efficiency ( Zhan et al, 2021 ).…”
Section: Characteristics and Function Of Exosomesmentioning
confidence: 99%
“…These results demonstrated that both MSC-Exo and MSC-BMP2-Exo had excellent cellular uptake efficiency. The higher cellular uptake efficiency for MSC-BMP2-Exo may be because the engineered MSC-BMP2-Exos increase the binding and interaction between exosomes and hMSCs, making it easier to be taken up by target cells [ 34 ]. As a therapeutic gene delivery vehicle, the biocompatibility of exosomes was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Human fetal bone marrow derived mesenchymal stem cells (hMSCs) and hepatocytes were seeded in 96-well plates at a density of 1 × 10 4 cells per well and allowed to attach overnight. MSC-BMP2-Exo or MSC-Exo (2 μg per well, 100 μl) was incubated with cells for 72 h, and this concentration was adopted according to the reference [ 34 ]. For liposome group, the cells were transfected with plasmid-lipid complex (0.1 μg plasmid per well) according to the instructions of Lipofectamine 3000 kit for 6 h and refreshed with culture medium.…”
Section: Methodsmentioning
confidence: 99%